History and Phenomenology of Islamic Education in Mualaf Villages - Syamsuddin, Syamsuddin (Islamic Studies and Development Center (ISDC) Universitas Negeri Padang, 2022)
The study was to analyze the driving factors of one's entry into Islam (muallaf), and the development of education in those